PUMPKIN JELLY CANDY GIVING "PORORO GUMMY" (Pumpkins and Carrots to Growth) TO INCREASE APPETITE IN TODDLERS - Sumarlina, Nenden; Rahayu, Anik; Sofa, Irma; Suhesti, Lia; Suryati, Ai; Danengsih, Nia; Erviani, Silvi; Lastari, Susi; Indrayani, Triana (International Journal of Engagement and Empowerment (IJE2), 2024)
Eating difficulties in early childhood, especially toddlers, is a significant nutritional challenge in Indonesia. If handled properly, these problems can help the growth and development of children. There is a need for practical solutions that can increase children's appetite in a way that appeals to both children and parents. This community service activity aims to improve the appetite of toddlers by introducing a healthy snack innovation called PORORO GUMMY (Pumpkins and Carrots to Growth). This activity was carried out at PAUD Kartini in West Bandung and involved children, parents, and school stakeholders. Gummy snacks are made from natural ingredients such as yellow pumpkin, carrots, honey, jelly, and lemon juice, which are rich in nutrients to support children's health. Nutrition education and snack-making demonstrations were also given to parents. The activity results show that PORORO GUMMY attracts children's interest and increases their appetite. Parents gain essential insights into providing healthy and nutritious food through nutrition education sessions and snack-making demonstrations. This activity offers practical solutions for children's eating difficulties and motivates families to adopt healthier eating habits. PORORO GUMMY is an effective and easy-to-implement alternative to increase the appetite of toddlers, as well as support their optimal growth and development